2011
DOI: 10.4028/www.scientific.net/kem.493-494.281
|View full text |Cite
|
Sign up to set email alerts
|

A New Natural Biomaterial: Sheep Dentine Derived Hydroxyapatite

Abstract: Hydroxyapatite (HA) is a particularly attractive material for bone and tooth implants since it does not only closely resemble human tooth and bone mineral but it has also biologically proven to be compatible with these tissues. The applications of pure HA are restricted to non load bearing implants due to the poor mechanical properties of HA. Biomaterials of synthetic HA are highly reliable but the synthesis of HA is often complicate and expensive. Bioceramics of naturally derived biological apatites are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For example, the use of egg-shell or sea-shell wastes, which represent the most abundant by-products of the food industry, has been found as a very promising sustainable resource to produce HA at a low cost with little impact to the environment [88,119,120,121]. Apart from the method of synthesis, the quality of non-synthetic HA (e.g., purity, grain size, properties) is strongly dependent on the biological source, location, age and fabrication process [1,55,92,93,94,99,100,104,109,111,112,116].…”
Section: Preparation Methods and Synthesis Routes Of Hydroxyapatitmentioning
confidence: 99%
“…For example, the use of egg-shell or sea-shell wastes, which represent the most abundant by-products of the food industry, has been found as a very promising sustainable resource to produce HA at a low cost with little impact to the environment [88,119,120,121]. Apart from the method of synthesis, the quality of non-synthetic HA (e.g., purity, grain size, properties) is strongly dependent on the biological source, location, age and fabrication process [1,55,92,93,94,99,100,104,109,111,112,116].…”
Section: Preparation Methods and Synthesis Routes Of Hydroxyapatitmentioning
confidence: 99%
“…In order to make samples suited for compression and microhardness testing, the powder was crushed between hardened steel dies. Sintered powder compacts were obtained at various temperatures: 1000, 1100, 1200, and 1300°C in air [ 42 ]. The findings of this study revealed that the HA material derived from sheep tooth dentine may be considered a promising source of HA for bioactive ceramics production.…”
Section: Biomaterials From Sheep-derived Wastementioning
confidence: 99%
“…Akyurt et al [63] produced HA from sheep teeth, by calcination and sintering at different temperatures (1000-1300 • C). Compression strength and microhardness measurements were performed and the obtained results were the best in the case of samples sintered at 1300 • C. This behavior was attributed to the F-content presence in the enamel structure.…”
Section: Extraction Of Ha From Mammalian Bonesmentioning
confidence: 99%